Nanoscale characterization of compound semiconductors using laser-pulsed atom probe tomography - Müller, M.; Saxey, David; Cerezo, A.; Smith, G. (2010)
Laser-pulsed atom probe tomography is introduced as a novel tomographic technique and its basic principles are explained. Atom probe provides 3-dimensional chemical maps with nanoscale resolution. For semiconductor research, needle-shaped atom probe samples are produced by focused ion beam lift-out and annular milling. An InAs buried quantum dot material was studied using laser-pulsed atom probe. The dot size, morphology and composition were evaluated as well as the wetting layers and interface composition. A laterally shifted In-rich core was visualised within the dots. Furthermore, a GeMn-based thin film was investigated to better-understand the mechanisms leading to the magnetic characteristics of this material system, which has potential applications as a magnetic semiconductor. We conclude that laser-pulsed atom probe has great potential for compound semiconductor research. © 2010 IOP Publishing Ltd.